2004
DOI: 10.1111/j.0962-1075.2004.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐inducible gene expression vectors for use in Drosophila melanogaster Schneider 2 cells

Abstract: Inducible, vector-based, expression systems that allow fine control of transgene expression are gaining more and more use in fundamental research as well as in therapeutic applications. In an effort to develop a tightly regulated heterologous expression system for Drosophila Schneider 2 cells, three different inducible reporter constructs were compared. These comprised six copies of the glucocorticoid response element fused to one of three distinct types of Drosophila gene promoters: (1) a TATA-box containing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…4C). As a positive control, we used a luciferase reporter gene under the control of an Hsp90-dependent glucocorticoid receptor-responsive promoter (37) and found that 5 M geldanamycin reduced dexamethasone-induced luciferase activity by 90% (Fig. 4C, left bars).…”
Section: Vol 79 2005mentioning
confidence: 99%
“…4C). As a positive control, we used a luciferase reporter gene under the control of an Hsp90-dependent glucocorticoid receptor-responsive promoter (37) and found that 5 M geldanamycin reduced dexamethasone-induced luciferase activity by 90% (Fig. 4C, left bars).…”
Section: Vol 79 2005mentioning
confidence: 99%